Leishmania tarentolae: A new frontier in the epidemiology and control of the leishmaniases - Mendoza-Roldan, Jairo Alfonso; Votýpka, Jan; Bandi, Claudio; Epis, Sara; Modrý, David; Tichá, Lucie; Volf, Petr; Otranto, Domenico (Transboundary and emerging diseases, 2022)
Leishmaniasis (or the leishmaniases), classified as a neglected tropical parasitic disease, is found in parts of the tropics, subtropics and southern Europe. Leishmania parasites are transmitted by the bite of phlebotomine sand flies and million cases of human infection occur annually. Leishmania tarentolae has been historically considered a non-pathogenic protozoan of reptiles, which has been studied mainly for its potential biotechnological applications. However, some strains of L. tarentolae appear to be transiently infective to mammals. In areas where leishmaniasis is endemic, recent molecular diagnostics and serological positivity to L. tarentolae in humans and dogs have spurred interest in the interactions between these mammalian hosts, reptiles and Leishmania infantum, the main aetiologic agent of human and canine leishmaniasis. In this review, we discuss the systematics and biology of L. tarentolae in the insect vectors and the vertebrate hosts and address questions about evolution of reptilian leishmaniae. Furthermore, we discuss the possible usefulness of L. tarentolae for new vaccination strategies.
Keywords: Psychodidae; Leishmania tarentolae; Sergentomyia; Mammals; Dogs; Europe; Leishmaniasis; hmyz - vektory; Evropa; savci; Animals; lidé; Humans; zvířata; Dog Diseases; Leishmania infantum; nemoci psů; Insect Vectors; psi; Sauroleishmania; leishmanióza; vaccine; leishmaniasis/leishmaniases